Kachinocoris brevipennis n.gen., n.sp. in Cretaceous Burmese Amber(Hemiptera: Heteroptera: Aradidae) - Heiss, Ernst (Zootaxa, 2012)
From an inclusion in Cretaceous Burmese amber a new genus of flat bugs, Kachinocoris n.gen., is described; its type species K. brevipennis n.sp. is illustrated.